Production of triploidy in red tilapia [Oreochromis mossambicus (Peters, 1852) X Oreochromis niloticus (Linnaeus, 1758)] - P.J., Pradeep (Institut Akuakultur Tropika, 2012)
Tilapias are widely distributed species in the tropical and subtropical regions of the world with high tolerance to different environmental conditions. This characteristic has made this species more attractive for culture.